Expansion of the interprofessional clinical practice of Primary Care nurses - Marina Peduzzi; Carla Aguiar; Aline Maciel Vieira Lima; Patrícia Martins Montanari; Valéria Marli Leonello; Mariangela Rosa de Oliveira
ABSTRACT Objective: To analyze the clinical practice of nurses in the interprofessional context of the Family Health Strategy. Method: Case study in a basic health unit of the city of São Paulo with a professional team of the Family Health Strategy and of the Family Health Support Center. Direct observation and interviews with thematic analysis and triangulation were conducted. Results: Four empirical categories were identified: interprofessional actions guided by the logic of the user's health needs; interprofessional actions guided by the logic of expediting service; interprofessional actions with a biomedical approach and interprofessional actions with an integral/holistic approach. Six interprofessional actions that indicated the expansion of the clinical practice of the Family Health Strategy's nurses were also identified. Conclusion: The results express the world trend of interprofessional practice and expansion of the scope of practice of different professions, particularly that of nurses, which requires consolidation based on the population's health needs.